Analisis Social Influence dalam Memediasi Luxury Brand Perception terhadap Purchase Intention - anisa nurfitriani; Asep Muhamad Ramdan; Faizal Mulia Z (Universitas Halu Oleo, 2023)
The fashion industry in Indonesia has experienced very rapid growth. Fashion is something that makes someone always want to change their appearance. Public awareness in seeking information about international fashion is one of the development factors in the fashion industry. The increasing human lifestyle poses a challenge to the fashion industry to always create new innovations. Because at this time the fashion industry is experiencing a fairly rapid increase, ranging from local to international brands and various models. The purpose of this study was to determine the mediating effect of Luxury Brand Perception in the relationship between Luxury Brand Perception and Purchase Intention. The research method used in this research is quantitative research with a descriptive and causal approach. The sample technique used is probability sampling by distributing questionnaires to 250 residents of Sukabumi City. The data analysis technique used is Structural Equation Modeling (SEM) with the help of AMOS version 24 software. The results of this study indicate that H&M's fashion products have succeeded in building good luxury brand perception, social influence, and purchase intention in the eyes of the people of Sukabumi City. Luxur brand perception has a significant positive effect on social influence of 10,106, social influence has a positive and significant effect on purchase intention of 5,929 and social influence mediates the relationship between luxury brand perception and purchase intention of 6,929. So it can be concluded that social influence acts as a mediator of the relationship between luxury brand perception and purchase intention. Keywords: Luxury Brand Perception, Social Influence, Purchase Intention.